Revestimento à base de gelatina contendo extrato de própolis vermelha na conservação de peito de frango - SOUSA, Antonia Mayara Brilhante de (2022)
Despite excellent sensory and nutritional characteristics and high market demand, refrigerated broiler meat has a short shelf life, due to physicochemical changes and microbial growth. Thus, the study aimed to evaluate the use of gelatin-based coating added with red propolis hydroalcoholic extract (RPE) in the conservation of refrigerated broiler breast. Initially, the RPE was analyzed for the total phenolics content, total flavonoids, antioxidant activity (DPPH and ABTS) and compounds identification by high performance liquid chromatography. The films were developed with different concentrations of RPE (30 and 60 g RPE/100 g of gelatin) and characterized as to the total phenolics contente, total flavonoids, antioxidant activity (DPPH and ABTS), color, transparency and water solubility. Broiler breasts were coated with gelatin coatings containing RPE (T1 - no coating; T2 - gelatin coating without RPE addition; T3 - gelatin coating with the addition of 30 g RPE/ 100 g and T4 - gelatin coating with added of 60g of RPE/ 100 g) and microbiological analysis, pH, color, lipid oxidation and weight loss determinations were performed. The consumer's attitude towards the four treatments was also evaluated. RPE showed high antioxidant capacity and the presence of the bioactive compounds liquiritigenin, calicosin, isoliquiritigenin, formononetin and biochanin A. The films containing the highest concentration of RPE were those that obtained the highest values of total phenolics, total flavonoids and antioxidant activity, also showing an increase in thickness and total color difference. Films added with RPE showed lower transparency and higher values of redness and yellowness when compared to the film without RPE, while moisture and water solubility were not significantly affected. The Pseudomonas count in the breast meat was <10 CFU/mL for all treatments, while for psychrotrophs, the addition of the gelatin-based coating reduced the proliferation of these microorganisms at 16 days of storage. For the mesophilic count, all treatments had a reduction at the end of storage, with the treatment with the highest RPE content showing the lowest value. RPE reduced the lipid oxidation values of broiler breast samples and the highest concentration reduced weight loss. For pH values, no significant difference was observed between treatments. The lightness and redness were not affected with the RPE addition, while the yellowness showed a significant increase. The highest total color difference values were observed for the coated samples. Regarding the consumer's attitude, the data showed that the product was well accepted. However, the participants showed some concern with the sensory characteristics such as possible changes in flavor and color of the product. Thus, the gelatin coating added with hydroalcoholic extract of red propolis, acted positively on the stability of the refrigerated broiler breast, showing a good acceptance by the consumers